Neonatal Abstinence Syndrome - Kirtisudha Mishra, K; Chopra, N; Dudeja, A; Datta, V; Saili, A; Dutta, A K (Kathmandu University Medical Journal, 2012)
Intrauterine exposure to drugs by mothers is not an uncommon finding ine our society. Due to the mother’s suppression of a medical history, the diagnosis of neonatal abstinence syndrome is often missed. We report a case of a term, female, newborn, who presented with the following features;e restlessness, inconsolable crying, along with sweating, vigorous sucking; andadiarrhoea. No conclusion was derived from routine investigations. Eventually, with a high degree of suspicion regarding maternal drug addiction, her history was reviewed and it was discovered that the mother was a heroin addict. The baby was diagnosed as a case of Neonatal Abstinence Syndrome. The neonate was successfully managed thereafter and discharged. http://dx.doi.org/10.3126/kumj.v8i4.6245 Kathmandu Univ Med J 2010;8(4):426-8